The Railway Traffic Shunting System - Pepevnik, Anton; Bogović, Blaž (Promet - Traffic&Transportation, 2003)
Economy demands quality peiformance of transport servicesfrom all spheres of the traffic system The shunting systemin railway transport is a part of the traffic system. The fact thatthe railways are an organization of special social interest makesits organization structure the more important for the economicdevelopment. Problems that appear in the development of theeconomic system clearly point out numerous irregularitieswithin the railways. The demand of quality transport servicesrequires rationality of transport which consequently requiresgreat changes in the field of traffic organization structure andexploitation of transport capacities.Elementary parameters of the quality evaluation of thetransport service in all traffic subsystems are: speed, safety andregularity of transport. The same parameters can be implementedas the basis of technical and exploitation characteristicsof traffic.The shunting system in railway traffic is affected by numerouselements which are interconnected and represent a uniformtechnological process. Subsequently, the shunting system isconsidered a uniform technological system. The characteristicsof such a system are apparent in the technical and technologicalprocess, e.g.:- integrality, i. e. characteristic of collective production oftransport services;- homogeneity of transport means;- standardization of means of integral transport.In the process of transport demands, maximum servicequality is incessantly required. However, maximum quality withcertain quantitative dimension in regard to mode, place andtime of the transport process requires engagement of transportmeans, which directly affects the costs. Therefore, it can be assertedthat the optimum lies between the maximum quantitativeand qualitative dimensions of transport services and in thedetermined time of minimum costs of means.